Stroke and Systemic Embolism After Successful Ablation of Typical Atrial Flutter - Expósito, Víctor (Clin Cardiol, 2016)
BACKGROUND: Following successful cavotricuspid isthmus (CTI) ablation during typical atrial flutter (AFL), anticoagulation therapy is usually withdrawn. However, potential subsequent atrial fibrillation (AF) in these patients may increase embolic risk in the long term. Embolic rates in this setting have not been clearly established. Our aim was to determine the incidence of stroke/systemic embolism following radiofrequency ablation of AFL, particularly in those without a prior history of AF. HYPOTHESIS: After succesful AFL ablation, patients may suffer embolic complications in the long‐term follow‐up, mainly due to asymptomatic AF episodes. METHODS: We conducted a retrospective analysis of all patients who underwent CTI ablation due to AFL in our center between 2006 and 2009. RESULTS: During the study period, 188 patients (mean age, 62.9 ± 8.6 years) underwent CTI ablation; 120 without prior AF were included in the study. At the end of the follow‐up period (mean, 5.0 ± 2.4 years), 56.7% of patients (68/120) remained in sinus rhythm, 7/120 experienced a recurrence of AFL, and 45/120 (38%) developed AF. Ischemic stroke occurred in 11 patients and systemic embolism in 1. Of these patients, 5 had documented AF following AFL ablation. In the remaining 7 cases, previously undiagnosed AF was subsequently diagnosed at the time of stroke/embolism. CONCLUSIONS: Patients with AFL who undergo successful ablation are by no means free from embolic complications during long‐term follow‐up, mainly due to a high rate of AF development. Given the difficulties in detecting AF and the uncertainty about the temporal relation of AF and stroke, oral anticoagulation may need to be continued in those patients with underlying stroke risk factors.